2004
DOI: 10.1213/01.ane.0000134811.27812.f0
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen in Children Undergoing Cardiac Surgery: Is It Effective?

Abstract: There is speculation based on laboratory tests and biochemical data regarding the functional integrity of the fibrinogen in young children. Recent investigations in adults have demonstrated that their fibrinogen level correlates with the thromboelastogram maximum amplitude (MA) after modification with a glycoprotein IIb/IIIa receptor blocker that uncouples platelet-fibrinogen interactions. We postulate that if the fibrinogen of young children is functionally intact then their fibrinogen levels should also corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 23 publications
3
33
0
1
Order By: Relevance
“…These findings were corroborated by a subsequent report of three-fold to four-fold increase in phosphorus content in fetal fibrinogen compared to adult fibrinogen [7]. In addition, specific thrombin clotting times were prolonged in newborns suggesting differences in polymerization of fibrin from 'fetal' fibrinogen [8], an observation that has led to a claim that fibrinogen in infants is 'dysfunctional' [9]. Observations that an increase in sialic acid content of fibrinogen is associated with a decreased rate of fibrin polymerization and the removal of sialic acid residues leads to increase in polymerization [10] provide a possible explanation for the differences in thrombin clotting times.…”
Section: Introductionsupporting
confidence: 62%
“…These findings were corroborated by a subsequent report of three-fold to four-fold increase in phosphorus content in fetal fibrinogen compared to adult fibrinogen [7]. In addition, specific thrombin clotting times were prolonged in newborns suggesting differences in polymerization of fibrin from 'fetal' fibrinogen [8], an observation that has led to a claim that fibrinogen in infants is 'dysfunctional' [9]. Observations that an increase in sialic acid content of fibrinogen is associated with a decreased rate of fibrin polymerization and the removal of sialic acid residues leads to increase in polymerization [10] provide a possible explanation for the differences in thrombin clotting times.…”
Section: Introductionsupporting
confidence: 62%
“…Unlike their patients, the subjects in this study were not healthy. Thus, their fibrinogen may have had a functional deficiency analogous to that in a study by Miller et al 2 and Deptula et al 3 . The von Clauss method relies on detection of the actual clot in excess of thrombin.…”
Section: Discussionmentioning
confidence: 63%
“…As we had only one animal of this age, it is not clear whether this result is only an exception or this very high concentration of fibrinogen is a typical feature of young fallow deer. In humans, it is reported that children can have a different structure and composition of fibrinogen leading to its decreased polymerisation (Miller et al, 2004;Monagle et al, 2010), but the level is usually comparable to that typical for adults (1.5-3.5 g/l). This result thus has to undergo further investigation and extended measurement on a more numerous sample of young animals to confirm or reject it.…”
Section: Discussionmentioning
confidence: 99%